ANALISIS EFEKTIVITAS BIAYA PENGGUNAAN OBAT PADA PASIEN RAWAT INAP PENYAKIT COVID-19 KATEGORI SUSPEK NON-COMORBID DENGAN TERAPI OBAT KOMBINASI ANTIVIRUS DAN ANTIBIOTIK DI SALAH SATU RUMAH SAKIT KOTA BANDUNG PERIODE JULI – DESEMBER 2021 - M. Hilmi Fathurrahman; Nela Simanjuntak; Neng Siti Sopiah (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. The cost of his treatment requires a large amount of money. This study aims to analyze the cost-effectiveness of drug use in hospitalized patients with COVID-19 in the category of non-comorbid suspects with combination antiviral and antibiotic therapy at the Bandung Hospital Period July – December 2021. This study uses a non-analytic descriptive method. Data collection was carried out retrospectively by accessing medical record data. Samples that met the inclusion criteria in this study were 48 patients. Cost-effectiveness analysis was carried out by calculating the Average Cost Effectiveness Ratio (ACER) and Incremental Cost Effectiveness Ratio (ICER), then a sensitivity analysis was carried out to determine the parameters that affect cost-effectiveness by increasing drug costs to 2.5%, 5%, 7.5%. . The results of the analysis show the use of combinations of antivirals and antibiotics in COVID-19 patients, namely there are 16 variables and the most cost-effective (cost-effective) treatment is the combination of ceftriaxone inj with oseltamivir obtained at ACER = Rp. 1.005.724, the combination of azithromycin with ceftriaxone inj. is obtained at ICER = Rp.-2.113,412. The results of the sensitivity analysis showed that there was no change in ACER and ICER even though the drug price was increased up to 7.5% and the combination of inj ceftriaxone with oseltamivir remained the most cost-effective.